Sustainability, Financial Performance And Creditworthiness In Small Enterprises: A Bibliometric Review With Insights For Kvic Entrepreneurship. (The Journal of Theoretical Accounting Research, 2026)
The Khadi and Village Industries Commission (KVIC) plays a crucial role in strengthening rural industrial development in India. In this context, sustainability, financial performance, and creditworthiness have emerged as key determinants of the long-term viability of small and micro-enterprises, especially in developing economies. This study examines how sustainability practices influence enterprise survival and how financial decisions shape performance and creditworthiness within MSMEs and KVIC-supported units. A systematic review was conducted using publications from 2015 to 2025, retrieved from Scopus and Web of Science databases. The SPAR-4-SLR protocol, PRISMA screening procedure, and VOSviewer-based bibliometric techniques were employed to identify intellectual structures, citation patterns, and thematic clusters. A total of 762 peer-reviewed articles were analysed, revealing six major themes: sustainable entrepreneurship, financial performance drivers, credit access and risk assessment, MSME resilience and growth, digital and institutional transformation, and enterprise sustainability frameworks. These themes highlight the multidimensional nature of enterprise sustainability and financial credibility within KVIC and MSME ecosystems. The study further proposes thematic directions for future research and offers insights relevant to scholars, policymakers, financial institutions, and practitioners working to enhance the sustainability and financial strength of small enterprises.